Are We Missing Osteoporosis-Related Vertebral Fractures in Men? - Sadat-Ali, Mir (Korean Society of Spine Surgery, 2011)
STUDY DESIGN: Retrospective study. PURPOSE: To assess the prevalence of osteoporosis related spinal fractures among Saudi Arabian males. OVERVIEW OF LITERATURE: Vertebral fractures are the most common complication of osteoporosis and is the first sign in both sexes and only 25 to 30% of radiographically observed vertebral deformities are recognized. METHODS: We analyzed the chest radiographs of consecutive Saudi Arabian men ≥ 50 years and who visited the emergency room of King Fahd University Hospital, Al Khobar, Saudi Arabia for a period of 12 months between November 1, 2007 and October 31, 2008. The site and type of fractures were classified as per the semi-quantitative technique. The other data retrieved from the medical records of patients included medications and clinical investigations for osteoporosis. RESULTS: Nine hundred seventy chest radiographs were performed during the study period and 876 radiographs could be analyzed. One hundred fifteen patients (13.1%) had 157 fractures. The mean age was 67.85 ± 10.1 years. There was more than one fracture in 21 patients (18.2%). The majority of fractures (n = 102, 64.9%) were observed in thoracic spine. Seventy-one (45.2%) fractures were classified as mild, 54 (34.4%) were moderate and 32 (20.4%) were severe. For 26 (22.6%) patients, the report of the radiologist highlighted the fracture. CONCLUSIONS: Saudi Arabian males with osteoporosis continue to be missed despite the high prevalence osteoporosis leading to vertebral fractures. We believe it is important for physicians to identify vertebral fractures early and treat then appropriately before an extremity fracture occurs with high mortality.